A informação e sua dimensão política na agenda de pesquisa em saúde no Brasil: uma análise a partir da produção acadêmica da Fiocruz - Martins, Eduardo Vieira (2005)
Science s accentuated development since 1950 resulted in a new structure of scientific research, which switched from an individual to a multidisciplinary activity, using more sophisticated technologies. The transformation of the scientific enterprise increased significantly the costs of scientific research in a way that, by the end of the 20th century, it is financed either by governments or large financial groups. The economic environment established in the world since the late 80s replace the international economic system s based in a model of material goods, which was predominant since the beginning of the capitalism, to a model based on immaterial goods, where a nation s wealth is measured by its capacity to generate knowledge and technology. This new knowledge based model is called Knowledge Society or Information Society since the basic instrument for its feasibility is the Information. In this context, the formulation of research agendas became, since the last decades of the 20th century, an essential issue for governments and research institutions that give important resources to scientific and technological research. In Brazil some enterprises have been trying, since the 90s, to establish research agendas. In the health sector these enterprises, initiated in 1994 with the first Health S&T Conference, have not achieved clear programs for the definition of health research priorities. In order to study how health institutions define, or not, their research agendas, the academic production of Fundação Oswaldo Cruz was analyzed on the period of 1989 to 2004, which is constituted by 1234 master thesis and 446 doctorate dissertations, adding up to a total of 1680 papers. Comparing the guidelines and the priorities formulated by international organisms such as the United Nations Millennium Development Objectives, and the priorities defined by the WHO and by the PAHO, and considering the guidelines that are not always explicit for such purpose, such as those from the Brazilian health department and FIOCRUZ, that the academic publication of FIOCRUZ has a research pattern that favors mainly the health issues of the country. These analyses from the perspective of Informational Science allow verifying the importance of Informational policy to the execution of scientific research as well as the formulation of health research agenda. The growth of research networks are based on intensive use of information in several dimensions. In formulating research agenda, information should be constructed from epidemiologic data and from the expectation of the people which the agenda is about. Information is a fundamental tool for the evaluation and sustainment of the research agenda, for its legitimacy is a result of permanent negotiation among several sectors of society, either being the scientific community, the policy formulators, the decision making, or the people